Симметрия и свойства записи генетической информации в ДНК - Гупал, А.М.; Гупал, Н.А.; Островський, А.В. (Проблемы управления и информатики, 2011)
Показано, що для пар основ можливі два види симетрії, але в природі реалізований один ефективніший спосіб запису і зчитування інформації. Доведено, що із симетрії послідовностей основ витікає симетрія коротких послідовностей — окремих основ. На базі моделі ланцюгів Маркова показано, що симетрія послідовностей основ витікає з симетрії пар основ. It is shown that for the pair of bases two types of symmetry are possible, but one more effective method of recording and reading information is realized in nature. It is proved that the symmetry of short sequences including separate bases follows from the symmetry of sequences of bases. On the basis of the Markov chains model, it is shown that the symmetry of sequences of bases follows from the symmetry of pairs of bases.